Mapping the field of constructed wetland-microbial fuel cell: A review and bibliometric analysis - Ji, Bin; Zhao, Yaqian; Vymazal, Jan; Mander, Ülo; Lust, Rauno; Tang, Cheng (Chemosphere, 2021)
The embedding microbial fuel cell (MFC) into constructed wetlands (CW) to form CW-MFC bears the potential to obtain bioelectricity and a clean environment. In this study, a bibliometric analysis using VOSviewer based on Web of Science data was conducted to provide an overview by tracing the development footprint of this technology. The countries, institutions, authors, key terms, and keywords were tracked and corresponding mapping was generated. From 2012 to September 2020, 442 authors from 129 organizations in 26 countries published 135 publications in 42 journals with total citation of 3139 times were found. The key terms analysis showed four clusters: bioelectricity generation performance, mechanism study, refractory pollutants removal, and enhanced conventional contaminants removal. Further research themes include exploring the biochemical properties of electrochemically active bacteria, emerging contaminants removal, effective bioelectricity harvest and the use, and biosensor development as well as scaling-up for real field application. The bibliometric results provide valuable references and information on potential research directions for future studies.
Keywords: mokřady; Bacteria; Waste Disposal, Fluid; odpad tekutý - odstraňování; Bioelectric Energy Sources; Electricity; odpadní voda; bibliometrie; Bibliometrics; zdroje bioelektrické energie; Electrodes; Wetlands; elektřina; Wastewater; elektrody